Statistical structure of the biological tissue scattering of laser field with the complex degree of coherence - Angelsky, P.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Diagnostic efficiency of differentiation of birefringence of rat’s biological tissues in different physiological states is studied in this research based on application of the correlation approach. Interrelation between coordinate distributions of complex degree of coherence (CDC) and changes in birefringence has been determined.